Penanggulangan Risiko Kualitas Sayuran Hidroponik Melalui Penerapan Diagram Ishikawa - Ramadhan, Dikri Syahru; Astutiningsih, Endang Tri; Rini, Neneng Kartika (Universitas Galuh, 2024)
Hydroponic vegetables are horticultural products that are increasingly in demand so that they are currently being improved in agriculture. The purpose of this study is to look at the type and number of defects in vegetables, specifically damage that requires improvement, influential aspects and appropriate solutions to improve the quality of vegetables in CV. Indonesian agrarian orange. Descriptive method is the main method used in this research. The data analysis method used is Ishiwaka diagram analysis and uses Checksheet tools and Pareto diagrams. The results showed 4 types of vegetable defects. Priority defects that must be repaired are torn leaves, rotten stems and rotten yellow leaves. Causes that affect the quality of vegetables include material, human, work methods and environmental factors. The right solution to use is (1) materials: choose and look for quality seeds and use hydroponic nutrients at the right dosage, (2) humans: improve skills and control workers (3) work steps: do more incentive prevention (4) Environment: maintenance of preventive pests is carried out in keeping the environment clean on green house land.